The Effect of Income Level and Social Altruistic Motivation of Teachers on Teaching Performance in PAUD Tawangmangu District - Putri, Dannella Ettiyana; Waluyo, Edi (Journal of Educational Sciences, 2025)
PAUD teachers have duties and responsibilities as well as altruistic social motivations in educating early childhood, which are not commensurate with the income they earn. This study aims to determine the effect of income level and social altruistic motivation of teachers on teaching performance in PAUD Tawangmangu District. The approach was quantitative, with a multiple linear regression method involving PAUD teachers selected through purposive sampling. Data collection was conducted using a Likert scale questionnaire that was tested for validity and reliability. The F-test results showed that income and altruistic social motivation significantly affected teaching performance (F = 11.763; sig. = 0.000). However, the t-test shows that only altruistic social motivation significantly affects teaching performance (t = 3.899; sig. = 0.000), while the level of teacher income has no significant effect (t = 1.104; sig. = 0.275). The adjusted R-squared value of 0.289 indicates that these two variables can explain 28.9% of the variation in teaching performance. This finding suggests that psychological aspects, particularly altruistic social motivations such as empathy, caring, and moral commitment, play a more critical role than economic factors in influencing ECD teachers' teaching effectiveness.